AL-QUR’AN DAN REALITAS SEJARAH UMAT MANUSIA - Ghozali Munir (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2012)
Al-Qur’an Is the word of Allah (God) which guaranteed the truth all time. His word righteous, including historical events mentioned in it, when the verses of Al-Qur’an understood in comprehensive, not partial. Al-Qur’an, the holy book contains complete teaching for human life, is as hudan (guidance), as al-Furqan (the difference between right and false, between right and wrong, between the benefits and madlarat), as az-zikr (a reminder that human do not get las in the sleaze and crime), and so forth. So the word of God is a functional, cerry out his word as a form of servitude to the Creator of human beings, providing a strong moral foundation and accurate for humans as the human stock/supplies in the world to get to the enjoy ment/happiness of the eternal here after.